MODELING PULL-OUT BEHAVIOR OF THE DEFORMED REBAR EMBEDDED INSIDE THE REINFORCED CONCRETE - Kohar Yudoprasetyo; Bambang Piscesa; Harun Alrasyid (Institut Teknologi Sepuluh Nopember, 2022)
Abstract: This study presents the modeling of the pull-out behavior of deformed bars embedded inside the reinforced concrete element. The simulation uses an in-house finite element package called 3D-NLFEA. Sufficiently small solid elements that consider the frictional resistance and mechanical interlocking between the bar thread and the concrete matrix were used in the simulation. The effect of concrete compressive strength, cover thickness, and stirrup configuration on the pull-out capacity of the modeled specimens are investigated thoroughly. The modeling found out that the 3D-NLFEA package can capture the bond-fracture process at the interface between the bars and concrete. The fracture that occurs in the concrete was dominated by tensile splitting failure. The presence of stirrups that confined the concrete and restrained the crack propagation significantly influences the pull-out capacity, cracking pattern, and failure behavior at the bar interface with the concrete. The analysis results from 3D-NLFEA are also compared with the 3D-RBSM analysis results available in the literature. From the comparison between the two packages, it can be concluded that the analysis result from 3D-NLFEA is somewhat more conservative compared to the 3D-RBSM.